International Corporate Governance Spillovers : Evidence from Cross-Border Mergers and Acquisitions - Albuquerque, Rui.; Brandao Marques, Luis.; Ferreira, Miguel; Matos, Pedro (Washington, D.C. : International Monetary Fund, 2013)
We develop and test the hypothesis that foreign direct investment promotes corporate governance spillovers in the host country. Using firm-level data on cross-border mergers and acquisitions (M and A) and corporate governance in 22 countries, we find that cross-border M and As are associated with subsequent improvements in the governance, valuation, and productivity of the target firmsa' local rivals. This positive spillover effect is stronger when the acquirer is from a country with stronger shareholder protection and if the target's industry is more competitive. We conclude that the international market for corporate control promotes the adoption of better corporate governance practices around the world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet